Swelling behavior of polystyrene networks in some aliphatic esters and linear polystyrene solutions - Sakar, Dolunay; Sarac, Ayfer; Cankurtaran, Ozlem; Karaman, Ferdane (SPRINGER, 2007)
Polystyrene networks were synthesized by free radical polymerization of styrene in the presence of dibenzoyl peroxide as an initiator, divinylbenzene as a crosslinker at 50 degrees C in toluene under nitrogen atmosphere. The swelling behavior of the synthesized polystyrene networks were studied at different temperatures in methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, tert-butyl acetate, and isopentyl acetate. Equations were given for the variation of the polymer-solvent interaction parameter, chi(12), as a function of reciprocal absolute temperature in the temperature range from 25 to 75 degrees C. Polystyrene networks were swollen in linear polystyrene solutions in toluene of different concentrations. Linear polystyrene samples were almost monodisperse and of high molecular weight. The equilibrium swelling degrees were evaluated using the Flory-Rehner theory. The relation of volume swelling ratio, q(v), to the volume fraction of the linear polymer in solution, phi, was evaluated and characterized by interaction parameter of crosslinked polystyrene with linear polystyrene, chi(23). The parameter chi(23) was found around zero as expected from mixtures of similar chemical structures by extrapolating the values of chi(23) at tested concentrations to zero solvent concentration.
Keywords: POLYMER NETWORKS; INTERACTION PARAMETER; ENTROPY PARAMETER; SOLVENT SYSTEMS; GELS; TEMPERATURE; ELASTICITY; COMPONENT; CHI; Polymer Science